Analisis Keamanan Jaringan Wireless menggunakan Metode Penetration Testing Execution Standard (PTES) - Satria Galang Saputra; Parga Zen, Bita; Abdurahman (Jurnal Sistem Informasi Galuh, 2023)
Network security has become a very important aspect along with the increase in the number of internet users. The Kalisapu Village Office, is a public service area located in Slawi District, Tegal Regency which currently uses Wireless Local Area Network (WLAN) network technology as a means of internet access and for various purposes, both administrative and other services to meet community needs. which only uses one wireless access point to access the internet network. Wireless networks must have good security to avoid various threats of crime, therefore it is necessary to analyze network security using the Penetration Testing Execution Standard (PTES) method, which is a framework or guide used as a reference for implementing network penetration. From the results of testing five times using the Kali Linux operating system virtual machine with the type of MAC authentication bypassing attack, each arp spoofing has a successful status while encryption cracking has three failures and two successes. Based on the test results, it can be interpreted that the wireless network security system is quite safe, but it is necessary to make some improvements to the system configuration and network topology to strengthen the security system and minimize the threat of crime.